Effects of icon size and location on speed and accuracy of SGD access. (1st October 2016) - Dukhovny, Elena; Zhou, YanYan
Abstract: Increasing speed and accuracy of communication via a speech-generating device (SGD) is an important clinical goal in augmentative and alternative communication (AAC). The current study, conducted with adults without disabilities using a within-subject experimental design, compared the effects of two different SGD trainings on speed and accuracy of locating words via an SGD interface. During size-centered training, participants were introduced to six large icons that completely filled an SGD screen. During location-centered training, participants were introduced to six small icons on a 40-location screen where other icons were hidden. After the training, participants were asked to find the trained items on a 40-location screen with all 40 icons visible. Accuracy and speed of response were analyzed, and the study found that participants located targets faster and more accurately following location-centered training vs. following size-centered training. If similar effects are found with individuals with complex communication needs, clinicians should consider implementing SGD grid designs that facilitate location-centered learning.